Challenges affecting prompt access to adequate uncomplicated malaria case management in children in rural primary health facilities in Chikhwawa Malawi - Larissa Klootwijk; Anthony Emeritus Chirwa; Alinune Nathanael Kabaghe; Michele van Vugt (BMC, 2019)
Abstract Background Reducing the burden of malaria highly depends on access to prompt and effective malaria diagnosis and treatment. The aim of this study was to identify challenges affecting prompt access to effective uncomplicated malaria case management in children below 10 years old in rural primary health care facilities in Malawi. Methods A cross sectional health facility survey was conducted in six primary health facilities in Chikhwawa district, Malawi. Officers-in-charge of health facilities were interviewed on availability of staff, supplies and drugs. All consecutive children presenting at the facility with fever or suspected malaria, aged 6 months to 10 years old, were eligible to participate in exit interviews. Exit interviews with participants' guardians assessed duration of illness, demographic information and distance travelled. Adherence to recommended malaria case management guidelines included performing malaria rapid diagnostic tests (mRDTs) in children with fever or suspected malaria and prescribing recommended weight-based dose of artemether-lumefantrine (AL) when mRDT was positive. Multivariate logistic regression was used to determine factors associated with prompt care seeking within 24 h of onset of illness. Results Health facilities were staffed by at least two health workers. Of 265 children screened, nine were excluded due to severe illness. Twenty-one percent of children presenting at a health facility with fever were not tested for malaria. Adherence to positive and negative mRDT results for those tested was 99.4, 95% CI [98.1-100] and 97, 95% CI [88.9-100], respectively. AL was prescribed as recommended by weight in 152 children (92.2%). Temporary stock outs of AL occurred in five of six facilities. In total, 146 (57, 95% CI [52.7-64.1]) guardians of patients sought care within 24 h after fever onset. Children aged 5 to 10 years were less likely to present within 24 h of fever onset than children below 5 years of age (unadjusted odds ratio 0.40, 95% CI [0.2-0.7]). Conclusion Adherence to malaria diagnosis and treatment guidelines was high. However, delayed care seeking and stock outs may affect prompt and effective malaria case management. Further qualitative work is required to determine, and address factors associated with delay in care seeking for fever.